2018
DOI: 10.3390/molecules23020492
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric Mixtures in Natural Product Chemistry: Separation and Absolute Configuration Assignment

Abstract: Chiral natural product molecules are generally assumed to be biosynthesized in an enantiomerically pure or enriched fashion. Nevertheless, a significant amount of racemates or enantiomerically enriched mixtures has been reported from natural sources. This number is estimated to be even larger since the enantiomeric purity of secondary metabolites is rarely checked in the natural product isolation pipeline. This latter fact may have drastic effects on the evaluation of the biological activity of chiral natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 111 publications
0
47
0
3
Order By: Relevance
“…The experimental ECD spectrum had to be multiplied by 20 to be comparable with the calculated ECD spectra, which implies about more than one order of magnitude difference. This indicated that the sample is probably a scalemic mixture with slight excess of the ( S ) stereoisome . Partial racemization of the chirality center is certainly aided by the benzylic position, since the C‐6 chirality center is α position to both a benzene and a furan ring.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental ECD spectrum had to be multiplied by 20 to be comparable with the calculated ECD spectra, which implies about more than one order of magnitude difference. This indicated that the sample is probably a scalemic mixture with slight excess of the ( S ) stereoisome . Partial racemization of the chirality center is certainly aided by the benzylic position, since the C‐6 chirality center is α position to both a benzene and a furan ring.…”
Section: Resultsmentioning
confidence: 99%
“…In the last decade, VCD spectroscopy has become a popular technique for the elucidation of absolute configurations of chiral molecules [31,32,33]. Therefore, in order to determine the stereochemistry of the asymmetrical carbon-17 of Campestrolide, the VCD spectrum of a sample containing 80% of compound 33 was measured in CD 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Once the relative configuration of Compound 1 was unambiguously assigned by NOESY analysis, vibrational circular dichroism (VCD) experiments and calculations were used to determine its absolute stereochemistry for the first time in the literature. VCD associated with density functional theory (DFT) calculations has been demonstrated as a powerful probe for chirality in natural products [14,15].…”
Section: Molecules 2020 25 X 3 Of 11mentioning
confidence: 99%
“…Many of the experiments carried out on these molecules were based on X-ray crystallography and degradation reactions, as in the case of neurolenin B, a sesquiterpene lactone that had its relative configuration assigned based on X-ray crystallographic data [9]. Nowadays, bidimensional NMR experiments, combined with vibrational circular dichroism (VCD) measurements and calculations, represent powerful complementary tools to unambiguously define both the relative and absolute configurations of a given molecule directly in solution [14,15].…”
Section: Introductionmentioning
confidence: 99%